Generation of three induced pluripotent stem cell lines carrying different variants of the BDNF (Val66Met) polymorphism - Horschitz, Sandra; Frank, Josef; Koch, Philipp (Stem cell research, 2023)
Brain-derived neurotrophic factor (BDNF) has been implicated in a multitude of neurodevelopmental processes including neuronal differentiation, axonal outgrowth, synaptic plasticity, or survival. One human-specific single nucleotide polymorphism (rs6265) in the BDNF gene causes a substitution of valine (Val) to methionine (Met) at codon 66 in the pro domain of the protein (Val66Met). This substitution is associated to reduced hippocampal volumes, poor performance on hippocampal-dependent memory tasks, and some mental disorders such as schizophrenia, depression or Alzheimer’s disease. Here we generated three iPSC lines from healthy donors, either homozygous (Val/Val and Met/Met) or heterozygous (Val/Met) for the polymorphism.
Online verfügbar 5 Dezember 2022
Gesehen am 28.03.2023